2014
DOI: 10.7812/tpp/14-004
|View full text |Cite
|
Sign up to set email alerts
|

A Business Case for Tele-Intensive Care Units

Abstract: Intensivists working these systems are able to more effectively treat ICU patients, providing better clinical outcomes for patients at lower costs compared with hospitals without a tele-ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 32 publications
(1 reference statement)
0
17
0
1
Order By: Relevance
“…6,7 Health care organizations that have invested time, money, and education in inpatient telemedicine monitoring have seen considerably higher adherence to best practices. [6][7][8] For example, tele-ICU implementation has been linked to increased use of evidence-based protocols for sepsis, ventilator-associated pneumonia, and blood transfusions, which has had a positive influence on quality improvement and patient care. 8 Tele-ICU departments also have collaborated with nursing and some have taken on the role of daily quality auditing.…”
Section: History Of Telemedicinementioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Health care organizations that have invested time, money, and education in inpatient telemedicine monitoring have seen considerably higher adherence to best practices. [6][7][8] For example, tele-ICU implementation has been linked to increased use of evidence-based protocols for sepsis, ventilator-associated pneumonia, and blood transfusions, which has had a positive influence on quality improvement and patient care. 8 Tele-ICU departments also have collaborated with nursing and some have taken on the role of daily quality auditing.…”
Section: History Of Telemedicinementioning
confidence: 99%
“…[6][7][8] For example, tele-ICU implementation has been linked to increased use of evidence-based protocols for sepsis, ventilator-associated pneumonia, and blood transfusions, which has had a positive influence on quality improvement and patient care. 8 Tele-ICU departments also have collaborated with nursing and some have taken on the role of daily quality auditing. 9 Because of this practice change, documentation of certain nursing quality metrics, such as use of restraints and incidence of pressure ulcers, has resulted in increased adherence to evidencebased practices and regulatory guidelines.…”
Section: History Of Telemedicinementioning
confidence: 99%
“…Studies assessing the financial impact of tele-ICU rarely describe their accounting methods, seldom use activity-based cost accounting, and acknowledge that the return on investment depends on how the technology is used (14). An exception is Lilly et al (15) who used activity-based cost accounting to report an increase in ICU cases per year, a reduction in cost per case, recovery of the initial capital cost in less than 1 year, and financial performance greater than the annual operating costs of their tele-ICU program.…”
mentioning
confidence: 99%
“…; Goran ; Coustasse et al. ), although more recent research has identified potentially large savings to hospitals (Lilly et al. ).…”
mentioning
confidence: 99%
“…Tele-ICU implementation is correlated with reductions in ICU and hospital LOS and mortality (Rosenfeld et al 2000;Breslow et al 2004;Zawada et al 2006Zawada et al , 2009McCambridge et al 2010;Franzini et al 2011;Lilly et al 2011Lilly et al , 2014Young et al 2011;Goran 2012;Kohl et al 2012;Wilcox and Adhikari 2012;Willmitch et al 2012;Kumar et al 2013;Sadaka et al 2013). Evidence on cost reductions from tele-ICUs for hospitals has been mixed (Franzini et al 2011;Goran 2012;Coustasse et al 2014), although more recent research has identified potentially large savings to hospitals (Lilly et al 2017).…”
mentioning
confidence: 99%